Factors Associated With Sustained Remission in Rheumatoid Arthritis in Patients Treated With Anti–Tumor Necrosis Factor. Issue 6 (8th May 2017) - Hamann, Philip; Holland, Richard; Hyrich, Kimme; Pauling, John D.; Shaddick, Gavin; Nightingale, Alison; McHugh, Neil
Abstract : Objective: Anti–tumor necrosis factor (anti‐TNF) antibody has revolutionized the treatment of rheumatoid arthritis (RA), and remission is now a realistic possibility for patients. Despite widespread use of anti‐TNFs, predicting which patients are most likely to attain a sustained good response to these treatments remains challenging. Our objective was to undertake a systematic review of the literature to evaluate existing evidence for demographic and clinical factors associated with the achievement of sustained remission in individuals with RA treated with anti‐TNF therapy. Methods: Embase, Medline, and the Cochrane Controlled Trials Register were searched along with studies identified from reference lists. Quality of studies was assessed using Newcastle‐Ottawa criteria. Meta‐analysis was undertaken where unadjusted odds ratios were available for the same demographic or clinical factors from at least 3 studies. Results: Six studies were identified. Concomitant methotrexate use was associated with an increased likelihood of achieving sustained remission. Greater baseline disease activity, tender joint count, age, disease duration, baseline functional impairment, and female sex were associated with reduced likelihood of achieving sustained remission. Conclusion: Factors predicting sustained remission are seldom reported. Evidence identified in this review supports current recommendations for methotrexate coprescription and highlights the negative impact of particular clinical and demographic features on the likelihood of achieving optimal response to anti‐TNF treatment. Sustained remission is clinically more relevant than point remission in RA. More widespread reporting of sustained remission will help clinicians set realistic expectations on likely long‐term treatment efficacy and could be an important tool for identifying patients suitable for dose optimization.